Negative electrode sheet and lithium ion secondary battery
By designing a negative electrode sheet that meets specific peeling force, diaphragm resistance and porosity ranges, the shortcomings of lithium-ion batteries in high power and fast charging performance are solved, and the high power, fast charging and long life characteristics of the battery are achieved.
Patent Information
- Application Number
- CN202410166040.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-02-05
AI Technical Summary
Existing lithium-ion batteries have shortcomings in high power and fast charging performance, especially in low-voltage states, and lack long-life characteristics.
By designing a negative electrode sheet, it includes a negative current collector and a negative electrode diaphragm compounded on the surface of the current collector, it meets the specific peeling force, diaphragm resistance and porosity range. The specific formula is 4≤-0.0164W2+212.77(1 -C)-151.66-T≤8.
It realizes the characteristics of lithium-ion batteries that take into account high power, high power discharge capability, fast charging performance and long life, and meets high performance needs such as eVTOL.
Smart Images

Figure BDA0004699968370000081 
Figure BDA0004699968370000091 
Figure BDA0004699968370000092
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a negative electrode plate and a lithium ion secondary battery. Background Art
[0002] At present, electric vertical takeoff and landing (eVTOL) equipment has received more and more attention, and lithium-ion batteries have become the best choice for eVTOL drives. In order to meet the needs of emergency landing, lithium-ion batteries must have high-power performance and still maintain high-power discharge capabilities when the battery is low. At the same time, they must also have characteristics such as fast charging performance and long life. Summary of the invention
[0003] In view of this, the technical problem to be solved by the present invention is to provide a negative electrode plate and a lithium-ion secondary battery. The lithium-ion battery prepared by the negative electrode plate provided by the present invention has the characteristics of high power, high-power discharge capability, fast charging performance and long life.
[0004] The present invention provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode film composited on the surface of the negative electrode current collector, wherein the negative electrode plate satisfies the formula shown in formula I:
[0005] 4≤-0.0164W 2 +212.77(1-C)-151.66-T≤8, Formula I;
[0006] In formula I, W is the peeling force between the negative electrode film and the current collector, in N / m;
[0007] T is the resistance of the negative electrode membrane, in mΩ;
[0008] C is the porosity of the negative electrode membrane.
[0009] Preferably, the value range of W is 10N / m to 19N / m; the value range of T is 3.7mΩ to 4.5mΩ; and the value range of C is 20% to 25%.
[0010] Preferably, the value range of W is 13N / m to 19N / m.
[0011] Preferably, the value range of T is 4.0mΩ~4.45mΩ.
[0012] Preferably, the value range of C is 20.2% to 23.2%.
[0013] Preferably, 4.9≤-0.0164W 2 +212.77(1-C)-151.66-T≤7.8.
[0014] Preferably, the negative electrode film comprises a negative electrode active material, a conductive agent, a binder and an auxiliary agent.
[0015] Preferably, the negative electrode active material is selected from graphite materials, and the graphite material is preferably one or more of artificial graphite, natural graphite, and composite graphite.
[0016] Preferably, the mass ratio of the negative electrode active material, the conductive agent, the binder and the auxiliary agent is 90-96:1-5:0.5-3:0.2-1.
[0017] The present invention also provides a lithium-ion secondary battery, comprising the above-mentioned negative electrode plate.
[0018] Compared with the prior art, the present invention provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode film composited on the surface of the negative electrode current collector, wherein the negative electrode plate satisfies the formula shown in Formula I:
[0019] 4≤-0.0164W 2 +212.77(1-C)-151.66-T≤8, Formula I;
[0020] In formula I, W is the peeling force between the negative electrode film and the current collector, in N / m; T is the resistance of the negative electrode film, in mΩ; and C is the porosity of the negative electrode film. The negative electrode sheet provided by the present invention can control the peeling force, film resistance and porosity of the electrode sheet, so that the lithium ion battery prepared by the negative electrode sheet that meets the range of the formula has the characteristics of high power, high power discharge capacity, fast charging performance and long life. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the fitting curve of W (peeling force) and T (film resistance);
[0022] Figure 2 It is the fitting curve of (1-C) and T (film resistance). DETAILED DESCRIPTION
[0023] The present invention provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode film composited on the surface of the negative electrode current collector, wherein the negative electrode plate satisfies the formula shown in formula I:
[0024] 4≤-0.0164W 2 +212.77(1-C)-151.66-T≤8, Formula I;
[0025] In formula I, W is the peeling force between the negative electrode film and the current collector, in N / m;
[0026] T is the resistance of the negative electrode membrane, in mΩ;
[0027] C is the porosity of the negative electrode membrane.
[0028] The peeling force between the negative electrode membrane and the current collector, the membrane resistance and the porosity all have different effects on the high power, fast charging performance and long life of the battery, but their effects are limited and mutually influential. Only when the formula 4≤-0.0164W is satisfied 2 +212.77(1-C)-151.66-T≤8, it can have high energy density and excellent power and cycle performance. 2 The value range of +212.77(1-C)-151.66-T is 4 to 8, and can be 4, 4.5, 5, 5.5, 5.8, 6, 6.5, 7, 7.5, 7.7, 8, or any value between 4 and 8, preferably any value between 4.9 and 7.8.
[0029] In Formula I, W is the peeling force between the negative electrode film and the current collector, in N / m. The value range of W is 10N / m to 19N / m, and can be 10N / m, 11N / m, 12N / m, 13N / m, 14N / m, 15N / m, 16N / m, 17N / m, 18N / m, 19N / m, or any value between 10N / m and 19N / m, preferably 13N / m to 18N / m. In the present invention, the peeling force (adhesion force) is generated by the intermolecular force, which is a van der Waals force, and the magnitude of the peeling force (adhesion force) depends on the distance between the binder polymer compound and the current collector.
[0030] When W (peeling force) is less than 10N / m, insufficient peeling force strength will cause the coating to fall off during the cycle, resulting in a decrease in capacity. When W (peeling force) is greater than 19N / m, the peeling force is affected by the binder content. As the binder content in the slurry increases, the W (peeling force) of the pole piece after rolling will increase. Since the main function of the binder is to adhere the electrode active material to the current collector, it is necessary to enhance the electronic contact between the electrode active material and the conductive agent and between the active material and the current collector, so as to better stabilize the structure of the pole piece. The peeling force between the coating and the current collector has an important influence on the cycle performance, rate and internal resistance of the lithium battery. Under the premise that the proportion of the main material remains unchanged, the increase in the binder content will reduce the content of the main material and the conductive agent, causing a decrease in T (membrane resistance) and a decrease in battery performance. Therefore, the appropriate peeling strength as an indicator has a certain guiding significance for the content of the adhesive.
[0031] In Formula I, T is the resistance of the negative electrode diaphragm, in mΩ; the value range of T is 3.7mΩ~4.5mΩ, which can be 3.7mΩ, 3.8mΩ, 3.9mΩ, 4.0mΩ, 4.1mΩ, 4.2mΩ, 4.3mΩ, 4.4mΩ, 4.5mΩ, or any value between 3.7mΩ~4.5mΩ, preferably 3.9mΩ~4.3mΩ. In the present invention, in order to meet the power requirements of fast charging and high power, it is extremely important to control the resistance of the battery. In addition, for the positive electrode of the high nickel system material, the humidity of the environment during storage is less than 2%. When the diaphragm resistance exceeds 4.5mΩ, the actual gram capacity of the prepared electrode will be 3~4mAh / g lower than the designed gram capacity, which is difficult to meet the high power and fast charging performance requirements. When the T (membrane resistance) of the negative electrode is less than 3.7mΩ, one way to reduce the membrane resistance is to increase the content of the conductive agent or improve the process control quality, but this will increase the cost of battery cell preparation. However, under the premise of meeting product requirements, the increase in cost is not desirable.
[0032] In Formula I, C is the porosity of the negative electrode membrane; the value range of C is 20% to 25%, and can be 20%, 21%, 22%, 23%, 24%, 25%, or any value between 20% and 25%, preferably 21% to 23%. In the present invention, lithium ions migrate and diffuse through the electrolyte in the pores. In the injection process, the electrolyte infiltrates into the pores of the pole piece. If the porosity is too small, the pole piece will not be fully infiltrated, and there will be a dry area. The electrochemical reaction cannot occur in this area, which will cause capacity loss and reduce the effective lithium ion conductivity, making it difficult to meet high power requirements. If only the mass of the active material is considered, an electrode with a high porosity may exhibit the best rate performance, but if the additional mass such as the current collector and the separator is further considered, the energy density will be greatly reduced. Therefore, these additional masses must be considered when evaluating the performance of electrodes or batteries.
[0033] When the C (porosity) of the negative electrode sheet is less than 20%, the C (porosity) is too low, which has a certain inhibitory effect on the deintercalation and extraction behavior of lithium ions, hindering the diffusion of lithium ions inside the material, reducing the diffusion rate, and easily generating a large polarization internal resistance during rapid discharge, resulting in poor rate discharge performance. The reduced porosity will reduce the sheet resistance T of the electrode sheet; when the C (porosity) of the negative electrode sheet is greater than 25%, excessively high C (porosity) will reduce the capacity of the battery cell.
[0034] Moderate peel strength is to ensure that during the battery cycle, the material will not fall off due to insufficient adhesion between the active material and the foil, which will cause a decrease in cycle performance and service life. The increase in peel strength is accompanied by an increase in the amount of adhesive, a decrease in the negative electrode main material content and the conductive agent content, and further causes a decrease in diaphragm resistance. High power is mainly achieved by increasing voltage and reducing internal resistance through lithium-ion battery materials. Among them, reducing diaphragm resistance and increasing porosity are to reduce internal resistance at the material level. The porosity of the electrode affects the specific resistance and charge transfer resistance of lithium ions during the diffusion process. The pores are enlarged and the resistance is reduced. Reducing diaphragm resistance is conducive to high-rate discharge and meets high power requirements. At the same time, the battery has good kinetic performance, which affects the long life of the battery cell. The peel force, diaphragm resistance, and porosity of the negative electrode sheet affect each other. Within a specific range, the battery cell can meet the balance of high power, fast charging performance and long life performance.
[0035] In the present invention, T is the diaphragm resistance of the negative electrode plate. By measuring the diaphragm resistance, the uniformity of the microstructure in the plate, the characteristics of the plate formulation, and the material properties can be determined, and the performance of the battery can be predicted.
[0036] Therefore, the relationship between W (peeling force) and T (film resistance) is first fitted to obtain the relationship between W and T.
[0037] Next, the relationship between (1-C) and T (membrane resistance) is obtained by fitting (1-C) and T (membrane resistance);
[0038] Then, the relationship between W (peeling force) and (1-C) can be established through T (film resistance) through the above two relationships;
[0039] Then, the relationship between W (peeling force) and (1-C) is substituted into the above relationship between W (peeling force) and T, and finally the relationship between the three is established through the film resistance. Further, by substituting the value range of W (peeling force), C (porosity) and T (film resistance) into the relationship, it can be obtained that 4≤-0.0164W 2 +212.77(1-C)-151.66-T≤8.
[0040] To meet the needs of eVTOL, when W (peeling force), C (porosity), and T (membrane resistance) meet the above conditions, there is a certain relationship between membrane resistance and porosity, and between membrane resistance and peeling force. The relationship between the three is established through membrane resistance: 4≤-0.0164W 2 +212.77(1-C)-151.66-T≤8. When it is in the range of 4 to 8, the lithium-ion secondary battery prepared therefrom can meet the requirements of eVTOL for high power, fast charging performance and long life.
[0041] In the present invention, the negative electrode film comprises a negative electrode active material, a conductive agent, a binder and an auxiliary agent. The negative electrode active material is selected from graphite materials, and the graphite material is preferably one or more of artificial graphite, natural graphite and composite graphite.
[0042] The present invention has no particular limitation on the types of the conductive agent, binder and auxiliary agent, and they can be any conductive agent, binder and auxiliary agent known to those skilled in the art that can be used for battery negative electrodes.
[0043] In the present invention, the mass ratio of the negative electrode active material, the conductive agent, the binder and the auxiliary agent is 90-96:1-5:0.5-3:0.2-1.
[0044] The present invention also provides a method for screening a negative electrode sheet that enables a lithium-ion battery to have the characteristics of high power, high power discharge capability, fast charging performance and long life, comprising the following steps:
[0045] The negative electrode active material, the conductive agent and the binder are mixed with a solvent to obtain a slurry;
[0046] The slurry is applied to the surface of the negative electrode current collector, dried and then cold pressed, so that the obtained negative electrode sheet satisfies the formula shown in formula I;
[0047] 4≤-0.0164W 2 +212.77(1-C)-151.66-T≤8, Formula I;
[0048] In formula I, W is the peeling force between the negative electrode film and the current collector, in N / m;
[0049] T is the resistance of the negative electrode membrane, in mΩ;
[0050] C is the porosity of the negative electrode membrane.
[0051] In the actual manufacturing process, the negative electrode membrane and current collector peeling force, membrane resistance and porosity of the lithium-ion secondary battery are controlled according to the above formula, and the above formula is satisfied, so that the negative electrode sheet with excellent performance is screened, so that the obtained battery has excellent power performance and cycle performance while taking into account energy density. At the same time, a large number of DOE experiments can be avoided, saving battery research and development time and cost.
[0052] The present invention also provides a lithium-ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is selected from the above-mentioned negative electrode sheets.
[0053] Wherein, the positive electrode sheet includes a positive electrode sheet current collector and a positive electrode film composited on the surface of the positive electrode sheet current collector, and the positive electrode film includes a positive electrode active material, a conductive agent, and a binder. The positive electrode active material is preferably a ternary positive electrode material or an iron-lithium material. Preferably, the positive electrode active material in the positive electrode sheet is one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphate containing olivine structure. The conductive agent is conductive carbon black, carbon nanotubes, etc., and the binder is preferably PVDF, with a mass ratio of 90 to 96:1 to 3:1 to 3. In some preferred embodiments of the present invention, the positive electrode collector is a carbon-coated aluminum foil, and the thickness of the positive electrode collector is 13μm.
[0054] The method for preparing the lithium ion secondary battery comprises the following steps:
[0055] The negative electrode sheet, the separator, and the positive electrode sheet are stacked in sequence and then wound to obtain a core, and the electrolyte is injected into the dry battery cell to obtain a lithium-ion secondary battery.
[0056] The present invention also provides an eVTOL, comprising the above-mentioned lithium-ion secondary battery.
[0057] The present invention provides a lithium-ion battery design and a lithium-ion battery that takes into account the characteristics of high power, fast charging performance and long life to meet the needs of eVTOL. The higher power requirement is to meet the needs of emergency landing and to maintain high power discharge capability under low power state. The higher fast charging requirement is to meet 80% charging in less than 15 minutes. The longer life requirement is to increase the battery life and reduce the frequency of battery replacement.
[0058] The negative electrode plate provided by the present invention can control the peeling force, membrane resistance and porosity of the plate, so that the lithium ion battery prepared by the negative electrode plate that meets the range of the formula has the characteristics of high power, fast charging performance and long life.
[0059] In order to further understand the present invention, the negative electrode sheet, lithium-ion secondary battery and eVTOL provided by the present invention are described below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0060] Examples and Comparative Examples
[0061] 1. Preparation of negative electrode sheet:
[0062] A graphite negative electrode material with a gram capacity of 350 mAh / g, a conductive agent (conductive carbon black), a binder (a mixed binder of CMC and PAA with a mass ratio of 2:1) and an additive (SBR) are mixed according to the specific mass proportions in Table 1 to prepare a slurry, the slurry is coated on the surface of the copper foil current collector, and the negative electrode sheet is obtained after drying.
[0063] The values of the peeling force, membrane resistance and porosity in the negative electrode sheet are shown in Table 2.
[0064] 2. Preparation of positive electrode sheet:
[0065] The ternary positive electrode material (ternary NCM811), the conductive agent (conductive carbon black), and the binder (PVDF) are mixed in a mass ratio of 97.5%:1.5%:1.0% to prepare a slurry, and the slurry is coated on the surface of a carbon-coated aluminum foil current collector with a thickness of 13 μm, and the positive electrode sheet is obtained after drying.
[0066] 3. Preparation of electrolyte
[0067] The fully dried lithium salt LiPF 6 It was dissolved in an organic solvent (a mixed solution of dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 7:3) to prepare an electrolyte with a concentration of 1 mol / L.
[0068] 4. The diaphragm is PE diaphragm.
[0069] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in sequence, with the separator being located between the positive electrode sheet and the negative electrode sheet, to obtain a bare battery cell;
[0070] The bare battery cell is placed in a battery shell, and after drying, an electrolyte is injected, and a lithium-ion secondary battery is obtained through vacuum packaging, standing, forming, and shaping processes.
[0071] 5. Performance Testing
[0072] The performance tests were conducted on the negative electrode sheets and lithium secondary batteries prepared in the above Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 2.
[0073] The specific test method is as follows:
[0074] (1) Peel force test
[0075] The test was conducted using the S1 series single-column electronic tensile testing machine from Dongguan Meigao Instruments Co., Ltd.
[0076] One side of a 3M double-sided tape was glued to a stainless steel plate (50mm*125mm), and the other side was glued to a 25mm*200mm negative electrode sheet to be tested. A roller was used to roll back and forth to successfully bond the negative electrode sheet, the double-sided tape and the stainless steel plate.
[0077] Then fix the stainless steel plate on a fixture of the electronic tensile testing machine, and another fixture of the electronic tensile testing machine clamps the free end of the pole piece to be tested at an angle of 180° to the stainless steel plate, and then pull the pole piece apart at a test rate of 50 mm / min.
[0078] The peeling force is measured by the force required to continuously peel the electrode strip from the stainless steel plate and converted into peeling strength. Note that the peeling line is perpendicular to the direction of the force. The value of the horizontal part of the curve in the tensile machine software diagram is the peeling force of the negative electrode.
[0079] (2) Diaphragm resistance
[0080] Tested using ACCFILM film resistance test system
[0081] A servo motor is used to apply pressure to the negative electrode, and the electrical signal is transmitted to the resistance test mechanism through the probe. At the same time, the high-precision thickness measurement mechanism measures the sample thickness. The data acquisition system collects and transmits data to the software end, and the data processing software performs preliminary processing and generates charts and tables, and finally forms the test data of the diaphragm resistance.
[0082] (3) Porosity of negative electrode membrane
[0083] The calculation formula is as follows:
[0084] Porosity = (1-ρ / ρa) × 100%;
[0085] Wherein, ρ: the packing density of the negative electrode membrane; ρa: the actual density of the negative electrode membrane.
[0086] (4) Battery capacity
[0087] Use 1C constant current and constant voltage charging and 1C discharge for capacity division.
[0088] (5) Battery energy density
[0089] Calculated using fractional capacity data.
[0090] (6) Cycle test process
[0091] At 25℃, use 1C charging and 1C discharging.
[0092] (7) Power test
[0093] The specific test steps are as follows:
[0094] (a) 1C constant current and constant voltage charging to the upper voltage limit;
[0095] (b) 1C discharge to 25% SOC;
[0096] (c) Discharge at constant power for 30 seconds to the lower voltage limit.
[0097] (8) Lithium Separation Window
[0098] The specific test steps are as follows:
[0099] (1) 1C volume;
[0100] (2) Determine the maximum charge rate tm C;
[0101] (3) 1C constant current and constant voltage charging to the upper voltage limit;
[0102] (4) 1C discharge for 54 min (10% SOC).
[0103] Use XC discharge to V2 = 0V, and record the charging time t (min), where V2 is the potential between the three electrodes and the negative electrode;
[0104] If t<42 / X min, reduce the charge rate XC (by 0.5 each time)
[0105] If t>42 / X min, increase the charge rate XC (increase by 0.2 each time)
[0106] End condition: If t = 42 / X min, then XC is the maximum charging rate and is named tm C.
[0107] Table 1 Negative electrode slurry raw material formula
[0108]
[0109]
[0110] Table 2
[0111]
[0112] As can be seen from Table 2, when the C (porosity) of the negative electrode sheet decreases, the sheet will not be fully wetted, and there will be a dry area. No electrochemical reaction can occur in this area, resulting in a decrease in capacity. At the same time, the reduction in the porosity of the electrode sheet will also reduce the membrane resistance and reduce the power. If only the mass of the active material is considered, an electrode with a high porosity may show a better rate performance, but if the additional mass such as the current collector and the diaphragm is considered at the same time, the battery energy density will be greatly reduced. Therefore, when evaluating the performance of the electrode or battery, the additional mass of the current collector and the diaphragm needs to be considered. In addition, when the C (porosity) of the negative electrode sheet is less than 20%, the C (porosity) is too low, which has a certain hindering effect on the deintercalation behavior of lithium ions, causing the membrane resistance to rise, resulting in a decrease in power, a decrease in lithium precipitation rate, and a decrease in cycle life; when the C (porosity) of the negative electrode sheet is greater than 25%, too high a C (porosity) will reduce the capacity of the battery cell.
[0113] Furthermore, moderate W (peeling force) strength is to ensure that during the battery cycle, the material is prevented from falling off due to insufficient adhesion between the active material and the foil, which causes a decrease in cycle performance and service life. The increase in W (peeling force) is accompanied by an increase in the amount of adhesive in the negative electrode membrane, which in turn leads to a decrease in the content of the negative electrode main material and the content of the conductive agent, thereby causing a decrease in the membrane resistance, resulting in a series of adverse effects such as power reduction, lithium precipitation rate reduction, and cycle life reduction. Therefore, it is necessary to balance the control of W (peeling force), T (membrane resistance), and C (porosity) parameters in the negative electrode sheet, which is beneficial to ensure that the battery has good dynamic performance while meeting high power requirements, thereby extending the life of the battery cell.
[0114] In the present invention, the relationship between W (peeling force) and T (film resistance) is obtained by fitting the data of Examples 1 to 3. The fitting curve is shown in Figure 1 , Figure 1 is the fitting curve of W (peeling force) and T (film resistance);
[0115] W (peel force) and T (film resistance) relationship: T = 10.26W 2 -73.388W+142.2(1)
[0116] The relationship between (1-C) and (membrane resistance) T is obtained by fitting (1-C) and T (membrane resistance). The fitting curve can be found in Figure 2 , Figure 2 is the fitting curve of (1-C) and T (film resistance);
[0117] The relationship between (1-C) and T: T = 0.0577*(1-C)-0.4212*(1-C)+1.5275(2)
[0118] The relationship between W (peel force) and (1-C) can be established through the above two equations via T (film resistance).
[0119] 10.26W 2 -73.388W+142.2=0.0577*(1-C)-0.4212*(1-C)+1.5275
[0120] Substituting the relationship between W (peeling force) and (1-C) into equation (1), we get
[0121] -0.0164W 2 +212.77(1-C)-151.66-T=0
[0122] The formula G = -0.0164W is obtained 2 +212.77(1-C)-151.66-T(4)
[0123] Substituting the value ranges of W (peeling force), C (porosity) and T (film resistance) into the relationship, we obtain a range of -0.0164W2+212.77(1-C)-151.66-T of 4 to 8.
[0124] In summary, it can be seen from the data results in Table 2 that only when the negative electrode plate satisfies the formula shown in Formula I and each parameter is guaranteed to meet a specific range, the prepared lithium-ion battery has the characteristics of high power, fast charging performance and long life.
[0125] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A negative electrode plate, characterized in that: It includes a negative electrode current collector and a negative electrode film composited on the surface of the negative electrode current collector, and the negative electrode film satisfies the formula shown in formula I: 4≤-0.0164W 2 +212.77(1-C)-151.66-T≤8, Formula I; W is the peeling force between the negative electrode film and the current collector, in N / m; the value range of W is 10N / m to 19N / m; T is the resistance of the negative electrode membrane, in mΩ; the value range of T is 3.7mΩ~4.5mΩ; C is the porosity of the negative electrode membrane; the value range of C is 20% to 25%.
2. The negative electrode sheet according to claim 1, characterized in that: The value range of W is 13N / m to 19N / m.
3. The negative electrode sheet according to claim 1, characterized in that: The value range of T is 4.0 mΩ to 4.45 mΩ.
4. The negative electrode sheet according to claim 1, characterized in that: The value range of C is 20.2% to 23.2%.
5. The negative electrode sheet according to claim 1, characterized in that: 4.9≤-0.0164W 2 +212.77(1-C)-151.66-T≤7.8。 6. The negative electrode sheet according to claim 1, characterized in that: The negative electrode film comprises a negative electrode active material, a conductive agent, a binder and an auxiliary agent.
7. The negative electrode sheet according to claim 6, characterized in that: The negative electrode active material is selected from graphite materials.
8. The negative electrode sheet according to claim 7, characterized in that: The graphite material is preferably one or more of artificial graphite, natural graphite, and composite graphite.
9. The negative electrode sheet according to claim 6, characterized in that: The mass ratio of the negative electrode active material, the conductive agent, the binder and the auxiliary agent is 90-96:1-5:0.5-3:0.2-1.
10. A lithium ion secondary battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 1 to 9.
Citation Information
Patent Citations
Negative plate, preparation method of negative plate, and lithium ion battery
CN113745451A
Negative pole piece and lithium ion battery
CN115602787A
Cited By
A 21650 cylindrical lithium-ion battery
CN122950570A